Greener Synthesis, In-Silico and Theoretical Analysis of Hydrazides as Potential Antituberculosis Agents (Part 1) - Suraj N. Mali; Anima Pandey; Bapu R. Thorat; Chin-Hung Lai (Chemistry Proceedings, 2021)
Since several decades, our healthcare burden has been increased due to tremendous cases of multidrug-resistant (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) infections, especially in tropical countries. In the present study, we have synthesized ten hydrazides with the use of the greener Chitosan-derived catalyst. This catalyst accomplished the said condensation reaction within 15–30 min at room temperature conditions. All our synthesized compounds showed stronger affinities against Mycobacterium tb and bacterial targets, especially towards 1d7u, than the standard drug ciprofloxacin. One of our compounds retained a lower toxicity (electrophilicity index (ω) 3.1304), low chemical hardness (η: 2.1740), and high softness (S: 0.4600). In the realm of the development of more potent, effective, and safe antituberculosis agents with an effective greener synthesis, our current study would provide more insights on potent analogues containing hydrazine motifs in them.